The legal unstoppability in money laundering schemes and its development due to the digital era regards offshores - Lauva, Estere (Riga Graduate School of Law, 2023)
The author chose to research this topic because of the unstoppability of money laundering due to digitalization and globalization. On the one hand, it has created new paths and ways on how to launder money, on the other hand, it has made the rules stricter, and governments are more careful and observant. The purpose of this study was to combine economic and law aspects regarding money laundering- to investigate: a) Money laundering schemes regarding offshores, their historical background, and development; b) to look at case law study and directive implementation- how the directive of the EU 2015/849 works regarding offshores and how case law has interpreted it; c) to research Digitalization's impact on money laundering on ways how digitization has changed the perspective in offshores and here the directive comes into play and its loopholes. The author chose to use a qualitative approach- a literature review and a case study. Five different cases which are related to EU directive 2015/849 and digitalization were chosen for this study. Digitalization plays an important role in money laundering- it influences not only new opportunities, but it gives new insights on how to control it. Tax havens- offshore have always been interesting for individuals and business owners because of their transparency, secrecy, and convenience to transfer and hide illicit funds. The EU regulation does not cover all aspects and has loopholes.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Tax law; offshore; EU directive 2015/849